P04.10 CDKN2A mutational status is associated with venous thromboembolism in patients with glioblastoma. (9th September 2021) - Kapteijn, M Y; Kaptein, F H J; Stals, M A M; van Duinen, S G; Taphoorn, M J B; Dirven, L; Koekoek, J A F; Klok, F A; Versteeg, H H; Buijs, J T
Abstract: BACKGROUND: Patients with glioblastoma have a high risk of developing venous thromboembolism (VTE). However, the underlying genetic risk factors remain largely unknown. Therefore, the aim of our study was to discover whether genetic aberrations in glioblastoma associate with VTE. MATERIAL AND METHODS: In this retrospective cohort study, all patients diagnosed with glioblastoma between February 2017 and August 2020 in two hospitals (Leiden University Medical Center and Haaglanden Medical Center) were included (n=341). Targeted DNA next-generation sequencing (NGS) had been performed of all glioblastomas for diagnostic purposes and included tumor mutational status of the genes ATRX, BRAF, CIC, FUBP1, H3F3A, IDH1, IDH2, PIK3CA, PTEN and TP53 and amplification/gain or deletion of BRAF, CDKN2A, EGFR, NOTCH1 and PTEN . Through extensive chart review, we collected data on VTE events (deep vein thrombosis and/or pulmonary embolism) three months before until two years after glioblastoma diagnosis, which were adjudicated by an independent investigator. Patients with cerebral vein thrombosis (n=3) and low quality NGS data (n=1; minimum reads/samples: <1.5M and/or minimum depth: <100 reads) were excluded. Cox regression analysis and competing risk analysis (CICR) were performed to compare patients that developed VTE with patients that did not. RESULTS: Of the 337 patients, 215 had died, 26 were diagnosed with VTE and 37 were lost to follow-up. CDKN2A deletion was found to associate most significantly with VTE (HR: 2.65, 95%CI: 1.18–5.94, p=0.018). Competing risk analysis confirmed this finding, demonstrating a 12-month adjusted cumulative incidence of 12.7% (95%CI: 7.5–19.3) compared to 5.2% (95%CI: 2.5–9.2) in patients with CDKN2A wild-type (p=0.013). No significant association was found between any of the investigated genes, including CDKN2A deletion, and death. CONCLUSION: This study demonstrates that CDKN2A deletion is associated with VTE in glioblastoma patients. Therefore, CDKN2A mutational status may be a promising predictor to identify patients with glioblastoma at high risk of VTE, who may benefit from thromboprophylaxis.